PENGARUH HARAPAN, KEPUASAN DAN SARANA FISIK TERHADAP LOYALITAS PELANGGAN (Studi kasus pada Usaha Jasa Warnet di Kudus) - Wijayanti, Ratna Yulia; Andriyanto, Irsad (BISNIS, 2016)
This study aimed to examine the effect of variable expectations,satisfaction, and physical facilities on consumer loyalty in the cafe business services both partial and multiple. The independent variables in this study is the expectation, satisfaction, and physical facilities as well as the dependentvariable is customer loyalty. Samples taken as many as 83 people with the sampling technique used was accidental sampling, data collection through interviews and questionnaire as well as documentation. As for processing the data using coding, editing and tabulatig and analysis using regression with t test and F-test using SPSS in data processing. By using the above analysis obtained by the research findings that the results of multiple linear regression analysis showed that expectations, satisfaction, and physical facilities partially have asignificant influence on customer loyalty. While jointly variable expectations, satisfaction, and physical facilities have a significant effect on customer loyalty by 87.2% ,. The implications, limitations and suggestions for future research arealso discussed in this article.